Relações afetivas e violência entre adolescentes em ambiente escolar: uma análise crítica - Dias, Maria Gabriela (2021)
This research discussed violence in affective relationships among adolescents in a school environment based on the critical theory of society, elaborated mainly by Theodor W. Adorno, Max Horkheimer, and Herbert Marcuse. This is an ex post facto research, which had as its source empirical data from other scientific productions. The main objectives of this study were: to investigate what the data from the research selected as sources indicate about the perception of adolescents about violence in affective relationships; to analyze the main characteristics identified by academic productions about violent relationships among adolescents; to find out what the research indicates about the school environment in the face of violence in affective relationships. The search was conducted on digital platforms: Brazilian Digital Library of Theses and Dissertations, CAPES Periodicals, Digital Library of USP, PUC/SP and UNICAMP, ANPEd and BVS, in which eight researches were selected, three theses and five dissertations, which best served as a source of information to the objectives of this dissertation. The data were organized and grouped into five categories of analysis according to the themes that stood out in appearance and frequency in the empirical data of the eight studies: naturalization and trivialization of violence; love and violence; gender norms; jealousy and control; school environment: adaptation and resistance. The main results obtained pointed to the invisibility of violence in affective relationships among adolescents, who, in turn, are submerged in the prevailing social structure, fostered by repression, domination and individualism, acting the same way with each other. The school environment was portrayed under two trends, one that presented the institution as only a reproducer of the current apparatus, and another that indicated as a place conducive to criticism and reflection, aiming to reduce violence in affective relationships